Propuesta pedagógica para la enseñanza de la literatura infantil basada en la caracterización de las prácticas docentes de lenguaje (2022)
The objective of this research Project was to design a pedagogical proposal to enhance Children Literature Teaching Process in second grade students at Liceo Feminine Mercedes Nariño, based on Spanish teachers’ practice characterization.